Tumor Macroscopic Morphology Is an Important Prognostic Factor in Predicting Chemotherapeutic Efficacy and Clinical Outcomes of Patients With Colorectal Neuroendocrine Neoplasms, One Multicenter Retrospective Cohort Study - Wang, Zhijie; An, Ke; Li, Rui; Liu, Qian (Frontiers in Endocrinology, 2021)
Background and Aims: Locally advanced and metastatic colorectal neuroendocrine neoplasm (NEN) is a rare disease with a dismal prognosis. We aimed to explore the value of the macroscopic morphology of NENs in the management of stage II-IV colorectal NENs, which has not been fully elucidated in previous reports. Methods: We retrospectively enrolled 125 eligible patients with stage II-IV colorectal NENs who were diagnosed between 2000 and 2020 from three Chinese hospitals. All were categorized into either protruding or ulcerative NEN groups through endoscopic evaluation of their macroscopic morphology. Clinicopathological data were collected and compared between the two groups. Survival analysis was performed to assess the survival outcomes between the two groups. Results: A total of 77 and 48 patients had protruding and ulcerative NENs, respectively. Patients with ulcerative NENs had a larger median tumor size (P<0.001) and higher median Ki-67 index (P<0.001), and a larger proportion of these patients had grade G3 disease (P=0.001) and poorly differentiated neoplasms (P=0.001), as well as higher frequencies of T3 and T4 tumors (P=0.006) than patients with protruding NENs. In addition, patients with ulcerative NENs showed a much lower response to first-line chemotherapy (20% versus 50%, P=0.030) and a worse 3-year progression-free survival (PFS) rate (19.7 versus 49.5%, P=0.001) and 3-year overall survival (OS) rate (30.7% versus 76.9%, P<0.001) than those with protruding NENs. The multivariate analysis results indicated that the macroscopic shape of NENs was an independent prognostic factor affecting both PFS (HR = 1.760, 95% CI: 1.024 – 3.026, P = 0.041) and OS (HR = 2.280, 95% CI: 1.123 – 4.628, P = 0.023). Conclusions: Ulcerative NENs were more malignant and chemotherapy resistant than protruding NENs. Tumor macroscopic morphology is a valuable prognostic factor for stage II-IV colorectal NENs.